Zn and Cd hyperaccumulating characteristics of Picris divaricata Vant. (23rd June 2009) - Tang, Yetao; Qiu, Rongliang; Zeng, Xiaowen; Fang, Xiaohang; Yu, Fangming; Zhou, Xiaoyong; Wu, Yudu
A field investigation and a pot experiment were conducted to study the Zn and Cd accumulation in Picris divaricata Vant. Under natural conditions, the average Zn and Cd concentrations in shoot of P. divaricata were 5911 and 246 µg g−1 (DW), with the maxima of 18, 339 and 585 µg g−1, respectively. Grown on a mixed soil for three months, P. divaricata accumulated up to 15, 183 μg g−1 Zn and 364 µg g−1 Cd in shoot with translocation factors of Zn and Cd all larger than one. Thus, P. divaricata could be identified as a new Zn and Cd hyperaccumulator found in China.